Prevalence of oral side effects associated with chemo and radiotherapy in head and neck cancer treatment: A cross-sectional study in Egypt - Dalia Mohamed abo el Fadel; Yasmine Kamal; Ashraf Hamed Hassouna; Amal Ali (Oral Oncology Reports)
Background: different treatment modalities used for treating head and neck cancer are associated with oral side effects that affect patients’ quality of life. This study aims to detect the prevalence of different oral side effects associated with chemo and radiotherapy in head and neck cancer. Methodology: A cross-sectional study was conducted on 294 head and neck cancer patients, clinical examination of the oral cavity was done in which oral mucositis, xerostomia, altered taste sensation, pain, oral fungal infections, and dysphagia were documented and graded as well as Edmonton Assessment Symptom Scale and University of Washington questionnaire v.4 (UWQOL). Results: The prevalence of oral side effects among 294 HNC patients was 93.9%. The most common one was oral mucositis 97.3% followed by xerostomia 84.4%, while 64.6% had dysphagia,53.7% complained of altered taste sensation, and 19% had oral fungal infections and pain mean score of 4. Postoperative radiotherapy is associated with Grade (2) oral mucositis and dysphagia, radical radiotherapy is associated with Grade (1) oral mucositis and pain while severe dysphagia is associated with combined therapy. According to quality of life questionnaire, the best score reported by UWQOL v.4 was shoulder pain while the worst score was for anxiety and mood. There was worsening of physical and social domains of quality of life with chemoradiotherapy and overall patient condition. Conclusion: Head and neck cancer patients suffer from severe oral side effects influenced by the treatment modality and stage of the tumor affecting their quality of life.